Demineralization adjacent to orthodontic brackets with fluoride releasing and conventional bonding agents - Gopinath Swapna; Sandeep Sharma; Vivek P Soni; Sandhya Tamgadge (Wolters Kluwer Medknow Publications, 2016)
Background: Enamel demineralization is an event which is always an integral part of fixed orthodontic treatment due to which fluoride releasing bonding agents are considered to be the most effective but have lower bond strength. Thus, this in vitro study has compared the degree of demineralization and bond strength of conventional and fluoridated bonding agents. Materials and Methods: One hundred and five extracted human premolars divided into Group I evaluated to study demineralization and Group II to evaluate bond strength. Group I was subgrouped into (A, B, C, and D and Group II was subgrouped into A, B, and C (n = 15 in each subgroup). All samples were bonded with metal brackets using Transbond Plus TM , Discover LC orthodontic adhesive TM , and Transbond XT TM ; the first two being fluoride releasing and the third being a conventional bonding composite. Group I samples were followed by sectioning and studied for mean depth of demineralization at the margins of the brackets using polarized microscopy. Group II samples were evaluated only for shear bond strength. Statistical analysis was done using ANOVA and Tukey's multiple comparison tests. Observation and Results: The mean depth of enamel demineralization and standard deviation was compared between subgroups A and C and B and C and the P value obtained was 0.02 in each group, suggestive of a considerably lesser degree of demineralization in fluoride releasing composites compared to conventional composite. Similarly, when shear bond strength was compared between subgroups A and C and B and C the P value obtained was 0.04 and 0.00, respectively. Thus, the shear bond strength of the fluoride releasing composites was lesser than that of the conventional composite but well within the clinically acceptable range. Conclusion: Fluoride releasing composites can be used to avoid demineralization around the brackets.